1985
DOI: 10.1136/bmj.291.6508.1534
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure in a national birth cohort at the age of 36 related to social and familial factors, smoking, and body mass.

Abstract: Blood pressure was measured in a birth cohort of 5362 subjects at the age of 36. The prevalence of hypertension in men (blood pressure greater than 140/90 mm Hg) was almost twice that in women, although women received treatment more often. Deaths of fathers of subjects from hypertensive and ischaemic heart disease were associated with significantly higher mean systolic and diastolic pressures in both sexes. Cigarette smoking was not strongly associated with blood pressure in men and not associated at ali in wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(71 citation statements)
references
References 24 publications
5
64
0
2
Order By: Relevance
“…[64][65][66][67] In a study from was associated with systolic BP in men only, in keeping with the Whitehall findings. 48 Men who had the US relative weight-adjusted BP was inversely related to parental occupation in black but not white attained a higher social class than their parents had higher pressures than those who retained the social children. 64 In Nigeria, an unadjusted inverse association between parental SES and systolic BP was class of their parents.…”
Section: Grade Occupation Ethnic Group Psycho-social Andmentioning
confidence: 93%
See 2 more Smart Citations
“…[64][65][66][67] In a study from was associated with systolic BP in men only, in keeping with the Whitehall findings. 48 Men who had the US relative weight-adjusted BP was inversely related to parental occupation in black but not white attained a higher social class than their parents had higher pressures than those who retained the social children. 64 In Nigeria, an unadjusted inverse association between parental SES and systolic BP was class of their parents.…”
Section: Grade Occupation Ethnic Group Psycho-social Andmentioning
confidence: 93%
“…Of 41 reports from developed countries which included reported in either sex in six of these studies and an In a Swedish study adjustment for treatment rates increased the SES differential in systolic BP. 36 In men 15,23,47,48,70,71 and the remainder either did not report sex-specific estimates or a difference between Paris treatment rates increased with occupational status but this did not account for the observed SES the sexes (Table 2). In developing or undeveloped countries, a direct association is more often found.…”
Section: Grade Occupation Ethnic Group Psycho-social Andmentioning
confidence: 97%
See 1 more Smart Citation
“…The second measurement of blood pressure was used in the analysis, using a correction factor for arm circumference (Maxwell et al, 1981). Hypertension was defined as systolic blood pressure Z140 mmHg and diastolic blood pressure Z90 mmHg, or if the survey member was taking medication for hypertension (Wadsworth et al, 1985).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In 1985, Wadsworth and his team reported that cohort members whose birth weight had been low had higher blood pressure as adults 1 . It was an early hint that fetal and infant growth shape adult health, a link that became known as the Barker hypothesis after David Barker, an epidemiologist at the University of Southampton, UK, who published a 1989 analysis of birth weight and health in a different cohort 2 .…”
Section: Lifetimementioning
confidence: 99%